Developments in Australian buddhism facets of the diamond - Spuler, Michelle, 1971- (Hoboken : Routledge, Taylor and Francis, 2014)
This book examines the adaptation of Buddhism to the Australian sociocultural context. To gain insight into this process of cross-cultural adaptation, issues arising in the development of Diamond Sangha Zen Buddhist groups (one of the largest Zen lineages in the West) in Australia are contextualised within the broader framework of the adaptations of Buddhist teachings and practices in other Westernised countries. The book also examines the methodological approaches currently used for studying this process and suggests a synthesis of the approaches used for studying convert and ethnic Buddhist.
Appendix A: Japanese Zen Buddhists groups in AustraliaAppendix B: Diamond Sangha affiliates world-wide; Appendix C: Agreements concerning the structure and function of the Diamond Sangha; Bibliography; Index
Description based upon print version of record.
Keywords: Buddhism -- Australia; Buddhism -- Australia; Buddhism; Spiritual life -- Buddhism; RELIGION / Comparative Religion; Electronic books